Acute Surgical Abdomen - Nader AL-Mane LRCP & SI MB BCh NUI FCARCSI; Faisal AL-Mane MB BCh MRCPI FRCPC; Zein Abdalla MB BS MS FRCA; Joe McDonnell MB BCh FFARCSI (SAGE Publishing, 2014)
Background . Pulmonary embolism is a common and potentially lethal condition. Most patients who die from massive pulmonary embolism do so within the first few hours of the event. The clinical manifestations of pulmonary embolism are nonspecific, which makes the diagnosis difficult. Case Report . We present a case of massive pulmonary embolism presenting as an acute surgical abdomen that underwent exploratory laparotomy and made a complete recovery. Why should an emergency physician be aware of this? Emergency department physicians should be aware that massive pulmonary embolism could present as an acute surgical abdomen in young healthy individuals.